Cooperation as an instrument of competence management to implement successful e-commerce business models. (1st January 2003) - Gersch, Martin
The example of German food home-delivery concepts shows that e-commerce business models differ from traditional retail business models in many ways. No potential participant can ever have all the necessary resources and competences to implement a competitive business model without external support. This is why cooperation seems to be a useful tool for competence management. The resource-based view will serve as theoretical background for the following analysis. The required and available competences of conceivable players can be identified, and isolation mechanisms of resources that have to be combined can be overcome. Features of resources can be identified that recommend special types of cooperations with the intention to establish and operate a business model. Up to now, the types of joint venture that have already been established in other industries and e-commerce business models have not yet been established in the German food home-delivery market. Some individual attempts to implement such types of business models were soon stopped.